(5+x)^2-36=0
(7x-11)^3=2^5+5^2+200
Tìm x biết : ( 7x - 11 )^3 = 2^5 . 5^2 + 200
( 7x - 11 )3 = 32 . 25 + 200
( 7x - 11 )3 = 800 + 200
( 7x - 11 )3 = 1000
( 7x - 11 )3 = 103
=> 7x - 11 = 10
7x = 10 + 11
7x = 21
x = 21 : 7
x = 3
=>(7x-11)^3=800+200=1000=10^3
=>7x-11=10
=>7x=21=>x=3
Vậy x=3
(7x - 11) mũ 3 = 2 mũ 5 x 5 mũ 5 + 200
\(\Rightarrow\left(7x-11\right)^3=\left(2\cdot5\right)^5+200=10^5+200\\ \Rightarrow\left(7x-11\right)^3=10000+200=10200\\ \Rightarrow7x-11=\sqrt[3]{10200}\\ \Rightarrow x=\dfrac{\sqrt[3]{10200}+11}{7}\)
Tìm x
a) 315 + (146 -x ) =401
b) (6x - 39 ) : 3 =201
c) 7x - x = 5 mũ 21 :5 mũ 19 + 3.2 mũ 2 - 70
d) 7x - 2x = 617 : 615 +44 :11
e) 0 :x = 0
f) 3 mũ x = 9
g) 9 mũ x -1 = 9
h) (2x +1 ) mux3 = 125
i) 2 mũ x - 15 =17
k) (7x - 11 )mũ 3 = 25 . 5 mũ 2 +200
l) 3 mũ x + 25 = 26. 2 mũ 2 + 2 . 3 mũ 0
m) 5 .2 mũ x + 4 .2 mũ x = 18 . 2 mũ 5
a) 315 + ( 146 - x ) = 401
<=> 146 - x = 401 - 315
<=> 146 - x = 86
<=> x = 60
Vậy x = 60
a. 2^x - 15 = 17
b. 27 . 3^x = 243
c. 3^x + 25 = 26 . 2^2 + 2 . 3^0
d. ( 7x - 11 )^3 = 2^5 . 5^2 + 200;
e. 3^x . 3 = 27
a) \(2^x-15=17\)
\(2^x=17+15\)
\(2^x=32\)
\(\Rightarrow2^x=2^5\)
\(\Rightarrow x=5\)
b) \(27.3^x=243\)
\(3^x=243:27\)
\(3^x=9\)
\(\Rightarrow3^x=3^2\)
\(\Rightarrow x=2\)
c) \(3^x+25=26.2^2+2.3^0\)
\(3^x+25=104+2\)
\(3^x+25=106\)
\(3^x=106-25\)
\(3^x=81\)
\(\Rightarrow3^x=3^4\)
\(\Rightarrow x=4\)
d) \(\left(7x-11\right)^3=2^5.5^2+200\)
\(\left(7x-11\right)^3=800+200\)
\(\left(7x-11\right)^3=1000\)
\(\Rightarrow\left(7x-11\right)^3=10^3\)
\(\Rightarrow7x-11=10\)
\(7x=10+11\)
\(7x=21\)
\(x=21:7\)
\(x=3\)
e) \(3^x.3=27\)
\(3^x=27:3\)
\(3^x=9\)
\(\Rightarrow3^x=3^2\)
\(\Rightarrow x=2\)
a) \(2^x-15=17\)
\(\Leftrightarrow2^x=17+15\)
\(\Leftrightarrow2^x=32\)
\(\Leftrightarrow2^x=2^5\)
\(\Leftrightarrow x=5\)
Vậy x = 5
b) \(27.3^x=243\)
\(\Leftrightarrow3^x=243:27\)
\(\Leftrightarrow3^x=9\)
\(\Leftrightarrow3^x=3^2\)
\(\Leftrightarrow x=2\)
Vậy x = 2
c) \(\left(7x-11\right)^3=2^5.5^2+200\)
\(\Leftrightarrow\left(7x-11\right)^3=800+200\)
\(\Leftrightarrow\left(7x-11\right)^3=1000\)
\(\Leftrightarrow\left(7x-11\right)^3=10^3\)
\(\Leftrightarrow7x-11=10\)
\(\Leftrightarrow7x=10+11\)
\(\Leftrightarrow7x=21\)
\(\Leftrightarrow x=21:7\)
\(\Leftrightarrow x=3\)
Vậy x = 3
d) \(3^x.3=27\)
\(\Leftrightarrow3^x=27:3\)
\(\Leftrightarrow3^x=9\)
\(\Leftrightarrow3^x=3^2\)
\(\Leftrightarrow x=2\)
Vậy x = 2
_Chúc bạn học tốt_
(7x - 11)3 = 25 . 52 + 200
3x + 25 = 26.22+2.30
(7x - 11)3 = 25.52 + 200
=> (7x - 11)3 = 800 + 200
=> (7x - 11)3 = 1000
=> (7x - 11)3 = 103
=> 7x - 11 = 10
=> 7x = 10 + 11
=> 7x = 21
=> x = 21 : 7 = 3
3x + 25 = 26.22 + 2.30
=> 3x + 25 = 104 + 2
=> 3x + 25 = 106
=> 3x = 106 - 25
=> 3x = 81
=> 3x = 34
=> x = 4
a)\(\left(7x-11\right)^3=2^5.5^2+200\) b) \(3^x+25=26.2^2+2.3^0\)
\(\left(7x-11\right)^3=32.25+200\) \(3^x+25=26.4+2.1\)
\(\left(7x-11\right)^3=800+200\) \(3^x+25=104+2\)
\(\left(7x-11\right)^3=1000\) \(3^x+25=106\)
\(\Rightarrow\left(7x-11\right)^3=10^3\) \(3^x=106-25\)
\(\Rightarrow7x-11=10\) \(3^x=81\)
\(7x=10+11\) \(3^x=3^4\)
\(x=\frac{21}{7}\) \(\Rightarrow x=4\)
\(x=3\) Vậy x = 4
Vậy x = 3
a 2^x-15=17
b (7x-11)^3=2^5*5^2+200
a ) 2 ^ x -15 = 17
2 ^ x = 17 + 15
2 ^ x = 32
2 ^ x = 2 ^ 5
=> x = 5
b ) ( 7x - 11 ) ^ 3 = 2 ^ 5 * 5 ^ 2 + 200
( 7x - 11 ) ^ 3 = 1000
( 7x - 11 ) ^ 3 = 10 ^ 3
=> 7x - 11 = 10
7x = 21
x = 3
3 ngũ x - 2 = 81
( 7x -11)ngũ 3 = 2 ngũ 5* 5 ngũ 2 +200
tìm x,biết
2 mũ x-15=17
(7x-11) mũ 3=25 nhân 5 mũ 2+200
(x +1) mũ 100-3 nhân (x+1) mũ 99=0
4x+5 nhân (x+3)=105
5 nhân(x-2)+10 (x+3)=170
1) \(2^x-15=17\)
\(\Leftrightarrow2^x=32=2^5\)
\(\Rightarrow x=5\)
2) \(\left(7x-11\right)^3=25\cdot5^2+200\)
\(\Leftrightarrow\left(7x-11\right)^3=825\)
\(\Leftrightarrow7x-11=\sqrt[3]{825}\)
\(\Leftrightarrow7x=11+\sqrt[3]{825}\)
\(\Rightarrow x=\frac{11+\sqrt[3]{825}}{7}\)
3) \(\left(x+1\right)^{100}-3\left(x+1\right)^{99}=0\)
\(\Leftrightarrow\left(x+1\right)^{99}\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\left(x+1\right)^{99}=0\\x-2=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-1\\x=2\end{cases}}\)
4) \(4x+5\left(x+3\right)=105\)
\(\Leftrightarrow9x+15=105\)
\(\Leftrightarrow9x=90\)
\(\Rightarrow x=10\)
5) \(5\cdot\left(x-2\right)+10\left(x+3\right)=170\)
\(\Leftrightarrow5\left[x-2+2\left(x+3\right)\right]=170\)
\(\Leftrightarrow3x+4=34\)
\(\Leftrightarrow3x=30\)
\(\Rightarrow x=10\)
cảm ơn bạn nhá NGUYỄN MINH ĐĂNG
(7x-11)^3 = 5^2 * 2^5 + 200
`(7x-11)^3 =5^2 *2^5 +200`
`=>(7x-11)^3 =25*32+200`
`=>(7x-11)^3 =800+200`
`=>(7x-11)^3 =1000`
`=>(7x-11)^3 =10^3`
`=>7x-11=10`
`=>7x=10+11`
`=>7x=21`
`=>x=21:7`
`=>x=3`
Đề yêu cầu làm gì em?